Fictional immorality and immoral fiction - Young, Garry (Lexington Books, 2021)
This book examines what, if anything, makes a depiction of fictional immorality-such as the murder, torture, or sexual assault of a fictional character-an example of immoral fiction, and therefore something that should be morally criticized and possibly prohibited.